Mencegah Pernikahan Dini Dan Stanting Sejak Dini : Strategi Edukasi Di SMP N 11 Seluma - Pradina, Gia; Manullang, Theresia Hanna Marsita Uli; Syaputra, Rio Mardenis; Yulianti, Syami; Lestari, Nimas Ayu (Jurnal Karya Nyata Pengabdian, 2025)
Early marriage remains a significant social issue frequently found among teenagers, including those in Seluma Regency. This problem is caused by various factors such as cultural norms, economic difficulties, low levels of education, and a lack of understanding about the negative impacts of early marriage, such as school dropouts, high-risk pregnancies, mental health issues, and stunting. This study aims to increase students’ knowledge and awareness about the dangers of early marriage and its relation to reproductive health and stunting through a health education program. The activity was carried out by KKN students from Universitas Dehasen Bengkulu at SMP Negeri 11 Seluma on May 14, 2025. The method used was a participatory education approach through direct material presentation, educational video screenings, and group discussions. The results showed that students’ initial understanding of early marriage was 49.17%. After the educational intervention, knowledge significantly increased to 74.83%. However, about 25% of students still lacked a deeper understanding, especially about the link between early marriage and reproductive health and stunting. This highlights the need for continued education efforts. The activity also succeeded in encouraging students to commit personally to delaying marriage and prioritizing the completion of their education. Therefore, this program can be seen as a preventive strategy to reduce the incidence of child marriage in Seluma Regency.